Ethics : Ethica Ordine Geometrico Demonstrata. - Spinoza, Benedictus de, 1632-1677 (Floating Press, 1951)
Ethics is a philosophical book written by Benedictus de Spinoza. Although published after Spinoza's death, in 1677, it is considered his greatest and most famous work. In it, Spinoza tries to set out a "fully cohesive philosophical system that strives to provide a coherent picture of reality and to comprehend the meaning of an ethical life. Following a logical step-by-step format, it defines in turn the nature of God, the mind, human bondage to the emotions ...